Teachers' job satisfaction levels - Demirtas, Zulfu (Elsevier Science Bv, 2010)
Job satisfaction is a positive or pleasant emotional state resulting from a person's appreciation of his/her own job or experience. The purpose of this research was identified the primary school teachers' job satisfaction levels. The research has been designed with the survey model. In accordance with this approach, the primary school teachers' job satisfaction levels have been measured. In the research, Teaching Satisfaction Survey (TSS) was used. According to results, teachers' job satisfaction levels are pretty high. In terms of age difference there is a meaningful difference in averages. The of group 36-40 age have the highest averages. On the other hand, the group of 41 and above age has the lowest averages. There are no meaningful differences in terms of the professional seniority and the branch of teaching variables. That the level of job satisfaction of teachers is very high affects positively the educational aims come true. It is expected that a school which has teachers with high level of job satisfaction gives qualified education and brings up successful students.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Teaching; job satisfaction; teaching job satisfaction; primary education teachers